ANALISIS SEMIOTIKA PESAN DAKWAH KIAI AFIFUDDIN MUHAJIR PADA MEDIA SOSIAL INSTAGRAM - Hariwati; Wawan Juandi (Maddah : Jurnal Komunikasi dan Konseling Islam, 2026)
Rapid advancements in information technology have given rise to various social media platforms. Instagram stands out as one of the most popular and frequently used platforms. A number of preachers da’i utilize social media to disseminate religious messages dakwah, one of whom is Kiai Muhajir Afifuddin. This study aims to describe the religious messages conveyed in posts on the Instagram account @muhajirafifuddin during the months of March and April 2025. The study employs a qualitative research method utilizing semiotic analysis. The object of the research consists of the religious messages found in posts on the @muhajirafifuddin Instagram account during the March–April 2025 period. Based on the analysis conducted, it is concluded that the religious messages in the posts on the @muhajirafifuddin Instagram account during this period comprised 8 messages in the Sharia (Islamic law) category, 7 messages in the Akhlaq (morality/ethics) category, and 2 messages in the Aqidah (faith/creed) category.